2021
DOI: 10.1016/j.icarus.2021.114409
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Saturn’s north polar color and cloud structure between 2012 and 2017 inferred from Cassini VIMS and ISS observations

Abstract: Cassini/ISS imagery and Cassini/VIMS spectral imaging observations from 0.35 to 5.12 µm show that Saturn's north polar region (70 • -90 • N) evolved significantly between 2012 and 2017, with the region poleward of the hexagon changing from dark blue/green to a moderately brighter gold color, except for the inner eye region (88.2 • -90 • N), which remained relatively unchanged. These and even more dramatic near-IR changes can be reproduced by an aerosol model of four compact layers consisting of a stratospheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 75 publications
3
17
0
Order By: Relevance
“…Early models constrained by the CCD spectral range were successful with broad vertical distributions. But multiple compact layers, even in the stratosphere and upper troposphere, can also match observations, as illustrated by Sromovsky et al (2020cSromovsky et al ( ,a, 2021. Evidence in flavour of compact layers, at least in the south polar region, are evident from the presence of antishadows (Sromovsky et al, 2020a) because physically thin layers are required to produce them.…”
Section: Vertical Extent Of Aerosol Layersmentioning
confidence: 81%
See 4 more Smart Citations
“…Early models constrained by the CCD spectral range were successful with broad vertical distributions. But multiple compact layers, even in the stratosphere and upper troposphere, can also match observations, as illustrated by Sromovsky et al (2020cSromovsky et al ( ,a, 2021. Evidence in flavour of compact layers, at least in the south polar region, are evident from the presence of antishadows (Sromovsky et al, 2020a) because physically thin layers are required to produce them.…”
Section: Vertical Extent Of Aerosol Layersmentioning
confidence: 81%
“…Karkoschka and Tomasko (2005) found a large latitudinal variation in the magnitude of the imaginary index but not in its shape. Sromovsky et al (2021) also found little spectral shape variation in the north polar hexagon region but a significant increase in amplitude between 2013 and 2016. There is a surprisingly large unexplained variability among the many results dis-played in Fig.…”
Section: Saturn's Chromophorementioning
confidence: 84%
See 3 more Smart Citations